Gambaran Penggunaan Media Komunikasi Sebagai Pusat Informasi Kesehatan - Burhanuddin, Nurfardiansyah; Fajrin, Muhammad Sofhyan; Zulfahmidah, Zulfahmidah; Aisyah, Windi Nurul (Yayasan Citra Cendekia Celebes, 2022)
Background and Purpose: Health information actually aims to collect, store and make patient health information available and easily accessible when needed. The purpose of this study is to describe the use of communication media as a health information center. Methods: This study is a descriptive research design. Data collected using a questionnaire. The data of this research are categorical variables from several groups so that it uses the frequency distribution test. Reference search results are entered into the Mendeley app using the Vancouver system. Results: shows a total sample of 103 people aged 20 years 5 people (4.9%), 21 years 13 people (12.6%), 22 years 57 people (55.3%), 23 years 23 people (22.3%) and 24 years 5 people (5.9%). Based on gender, 88 people (85.4%) and 15 women (14.6%) were obtained. Conclusion: respondents often receive health information through social media, respondents also find it useful after getting information and users also usually continue to return health information received to other users. Keywords: health information, students, health